Perlindungan Terhadap Pengetahuan Tradisional Makanan Khas “Gulai Ikan Mungkus” Sebagai Kekayaan Intelektual Komunal Kabupaten Kaur - Winata, Nugraha Pandu; Susetyanto, Joko; Ganefi; Hamdani (UNIB Press, 2023)
The purpose of this research is to find out: 1). What are the efforts to protect Traditional Knowledge of the Gulai Ikan Mungkus special food carried out by the Kaur Regency Regional Government, Kaur Regency traditional restaurant entrepreneurs, and Kaur Regency Communities, and 2). What is the role of the Kaur Regency Government in Registering the Gulai Ikan Mungkus Special Food as Traditional Knowledge of Kaur Regency. This research is an empirical legal research, using a sociological juridical approach. Data collection was conducted by interviewing selected respondents/samples, observation, and document study. Data processing was started with coding and continued with data editing. After all the relevant data was complete and there were no errors, then data analysis was conducted using qualitative analysis. To further be described in order to answer the research objectives. The research results showed that: 1). the effort to protect the Traditional Knowledge of the Gulai Ikan Mungkus special food conducted by the Regional Government of Kaur Regency was by collecting data on restaurant actors who sell the Gulai Ikan Mungkus special food to be included in the festival events held by the Kaur Regency Government, appealed to all elements of society to register the Gulai Ikan Mungkus special food to the Education and Culture Office, cultivate Mungkus fish, as well as introduce this special food to foreign tourists came to visit Kaur Regency. Efforts to protect traditional restaurant business actors while maintaining the noble values and taste of Gulai Ikan Mungkus traditional food, 2). The Kaur Regency Government has not played a role in registering the special food Gulai Ikan Mungkus.